Environmental Justice and Pedestrianism: Sidewalk Continuity, Race, and Poverty in New Orleans, Louisiana. Issue 1 (2016) - Lowe, Kate
Extensive research documents the unequal distribution of benefits and harms from automobiles and transit, but little transportation research on environmental justice considers differing access to and quality of pedestrian infrastructure by race and income. This study uses an audit of sidewalk continuity adjacent to bus stops in New Orleans, Louisiana, to determine whether sidewalk continuity had a relationship to census tract-level poverty and racial composition. The analysis shows that minority populations and, to some extent, populations living in poverty are significantly associated with worse sidewalk connectivity. Disparities in the quality of pedestrian infrastructure warrant more attention, and future research could examine potential disparities in differing locations, as well as the role of governmental and nongovernmental actors in sidewalk provision.